Dependability and Organizational Bankruptcy: An Application of Agency and Prospect Theory - D'Aveni, Richard A. (Management Science, 1989)
This paper proposes and tests a new model of organizational bankruptcy based on agency and prospect theory. The paper argues that debtors with unprestigious top managers, low liquidity and high leverage signal that they will be undependable exchange partners. The model proposes that survival is contingent on maintaining an acceptable, minimum level of these financial and managerial assets. If a firm falls below that threshold level, it has a higher probability of bankruptcy because creditors withdraw their financial support from the debtor. Consistent with agency theory, this implies that bankruptcy can be viewed as the legal resolution of severe shareholder-creditor conflicts about the levels of financial and managerial assets that the debtor should maintain. This new model proposes that maintaining a minimum level of these assets is a necessary, but not sufficient, condition for bankruptcy. Some undependable firms delay bankruptcy by using strategies that create the hope that they will become dependable in the future. According to prospect theory, these strategies work because creditors wish to avoid recognizing significant losses, and thus take on more risk than they might otherwise assume.